Prevention of sepsis in patients with impaired splenic function (Research, Society and Development, 2023)
Asplenia refers to the complete loss of spleen function, while hyposplenism refers to the partial loss of splenic function, which may be of primary or secondary origin. The spleen is a secondary lymphoid organ, however, it is also connected with blood circulation. This organ houses a variety of cells, such as T and B lymphocytes, macrophages, dendritic cells, cytokines and antibodies essential for the development of immune responses. In this context, sepsis represents a risk for this group of patients and should be avoided with prophylactic measures, with the majority of infections being caused by encapsulated bacteria. To this end, a literature review was prepared with the main evidence on the prevention of sepsis in patients with asplenia/hyposplenia, using 17 materials from the SciELO, PubMed, Web of Science, Scopus, Cochrane Database of Systematic Reviews (CDSR) databases, EBSCOhost, Virtual Health Library (VHL) and UpToDate. Prevention of sepsis in patients with asplenia or hyposplenia has been shown to involve a combination of vaccination, antibiotic prophylaxis, patient education, and appropriate medical monitoring. It is essential that patients follow medical advice and are aware of the risks and preventive measures necessary to protect their health. Due to the lifelong risk associated with infection in these patients, efforts are focused on improving the quality of care provided to children and adults with restricted splenic function, in addition to ongoing research aimed at alternatives for preventing and treating this condition.